Do people feel less at risk? Evidence from disaster experience - Gao, Ming; Liu, Yu-Jane; Shi, Yushui (Journal of Financial Economics, 2020)
Past studies typically have focused on whether people perceive more rare risk after experiencing catastrophic disasters. We show that people can also feel less risk with unexpected lucky disaster experience. By exploring a novel identification strategy based on households’ expectations, we find that households perceive less (more) risk when they experience disasters that have lower (higher) fatalities than what was expected. This opposite experience effect of rare disasters is substantial. A one standard deviation increase in the negative (positive) experience shock is associated with a 1.71% decrease (a 1.31% increase) in the life insurance-to-portfolio ratio. We discuss three possible mechanisms to account for our empirical findings: incomplete information learning, salience theory, and change in risk preferences.